2020
DOI: 10.1111/pedi.13157
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the knowledge and attitudes of school staff related to diabetes care at school: The 10th year of the “diabetes program at school” in Turkey

Abstract: The aim of this study was to measure the knowledge and attitudes of school staff regarding care in school for children with type 1 diabetes and to evaluate the contribution of the “Diabetes Program at School”(DPS). The data were collected through an online survey consisting of 55 questions, which included 39 knowledge and 16 attitude questions. The survey was delivered to the participating school staff via a link. A total of 55,677 people who completed 100% of the survey were included. Of the participants, 76%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…When asked whether there is a lunch for students who are at school all day, 19.2% of the participants answered ''Yes''. This rate was found to be 40% in another study conducted in Turkey [4]. Some of the important results of our study are that most of the teachers do not know the practices to be done for low blood sugar, and they are not aware of the effect of insulin and the way it is applied.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…When asked whether there is a lunch for students who are at school all day, 19.2% of the participants answered ''Yes''. This rate was found to be 40% in another study conducted in Turkey [4]. Some of the important results of our study are that most of the teachers do not know the practices to be done for low blood sugar, and they are not aware of the effect of insulin and the way it is applied.…”
Section: Discussionmentioning
confidence: 59%
“…Teachers were asked to attend the training and take part in diabetes management. In a study that audited the effectiveness of the "Diabetes Program at School" and evaluated the knowledge and attitude scores of teachers throughout Turkey, the lowest scores were found in Central Anatolia and Southeastern Anatolia regions, and it was determined that the level of knowledge and awareness of school staff about T1DM showed regional differences [4]. In our study, we evaluated the knowledge level and awareness of teachers in public and private schools operating under the Provincial Directorate of National Education in the province of our city in the Central Anatolian region, and the adequacy of the school equipment, with a scale consisting of 3 parts.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent country-level study involving 55,677 teachers, school administrators and school nurses, 73% of the participants reported that they had heard about the Diabetes at School Program, 75% stated that their knowledge had increased thanks to this program, and 50% stated that their self-confidence had increased. The results of this study showed that nurses and the staff who had students with T1D in their classrooms/schools (women in particular), had higher scores ( 24 ). However, lower scores were noted in the northern and eastern regions of Turkey, where even in schools which had students with T1D, school staff did not have enough knowledge to determine carbohydrate count and bolus doses, and efforts were needed to continue a positive attitude change.…”
Section: Discussionmentioning
confidence: 76%
“…Five out of the six independent predictors for good teachers’ knowledge about Type 1 Diabetes in our study were related to the practical experience gained from intimate contact with diabetic patients or being themselves having diabetes. Teachers who had previous experiences with children with diabetes showed in other research a much higher level of knowledge than those who did not [ 11 , 24 ].…”
Section: Discussionmentioning
confidence: 99%